Struktur Organisasi dan Efektivitas Manajemen Koperasi Pembangunan Usaha Sumatera Barat - Rahmi, Yuri; Latifannisa, Nuri; Wardiman, Jery; Yulhendri, Yulhendri; Cerya, Efni; Nofriansyah, Nofriansyah (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research investigates the organizational structure and effectiveness of management at Koperasi Pembangunan Usaha Sumatera Barat, utilizing qualitative methods such as observations and interviews. The cooperative's hierarchical framework, which encompasses the General Assembly, managers, and staff, ensures efficient decision-making and consistent implementation of policies. With an experienced manager at the helm, the cooperative places great emphasis on cooperative education and character development, cultivating a culture of honesty and integrity that is crucial for long-term sustainability. The cooperative upholds familial principles and promotes mutual trust, employing a selective recruitment process to ensure alignment with its core values. The cooperative's empathetic approach to problem-solving, which includes pawn systems, collateral sales, and deadline extensions, highlights its ability to handle challenges with compassion. Financial management practices, such as employing professional accounting services and providing quarterly financial reports, guarantee transparency and accountability. Furthermore, the distribution of 40% of profits through the Surplus of Cooperative Efforts (SHU) demonstrates a commitment to fairness and the collective well-being of its members. The study concludes that the cooperative's well-defined organizational structure significantly enhances the effectiveness of its management. The hierarchical organization facilitates transparent operations, while leadership driven by values fosters a cohesive and sustainable culture. These findings hold valuable insights for other cooperatives seeking to enhance their management effectiveness through structured organization and value-based practices.